Implementasi Infografis sebagai Media dan Pendukung Pembelajaran Bahasa Inggris - Sudewi, Putu Wahyu; Putri, Andi Mega Januarti; Imansari, Nurul (Universitas Nusantara PGRI Kediri, 2025)
English plays a crucial role as a global language that needs to be learned from an early age, as it opens up global opportunities and enhances cross-cultural communication. However, children in the Tamo Dhua area face challenges in learning English due to a lack of access to engaging and effective materials. This activity aims to optimize children's understanding of English through the use of visually appealing infographics. Infographics are used to simplify information and make learning more interactive. The methods applied include material development, infographic creation, and classroom implementation. Observation and evaluation results show that infographics help children better understand basic English vocabulary and increase their engagement in learning. The children showed improvement in remembering and using English words and actively participating in activities.